2017
DOI: 10.1007/s10995-017-2325-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Familial Coexistence of Child Stunting and Maternal Overweight with Indigenous Women in Guatemala

Abstract: Objectives This study investigated the association of the familial coexistence of child stunting and maternal overweight with indigenous women in Guatemala. Methods We selected 2388 child-mother pairs from the data set of the Living Standards Measurement Study conducted in Guatemala in 2000. This study examined the association between maternal and household characteristics and the nutritional status of children aged 6-60 months and mothers aged 18-49 years by using multivariable logistic regression models. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…DFM (Dual forms of malnutrition) is defined as a household in which one person is overweight while another is underweight, which reflects the dual burden of overnutrition and undernutrition within a single household [ 1 ]. Prior studies have documented DFM at the household level [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Demographic Health Surveys from eight Latin American, 23 African and five Asian countries from 1991-1998 showed that DFM stunted children aged 0-60 months, and the percentage of overweight mothers ranged from 0-15%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFM (Dual forms of malnutrition) is defined as a household in which one person is overweight while another is underweight, which reflects the dual burden of overnutrition and undernutrition within a single household [ 1 ]. Prior studies have documented DFM at the household level [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Demographic Health Surveys from eight Latin American, 23 African and five Asian countries from 1991-1998 showed that DFM stunted children aged 0-60 months, and the percentage of overweight mothers ranged from 0-15%.…”
Section: Introductionmentioning
confidence: 99%
“…Other previous studies focused on different age-classified pairs of subjects as stated in each DFM group, including child-mother [ 13 ] and adolescent-mother pairs [ 14 ]. However, most DFM studies have used child-mother pairs as both populations are considered to be vulnerable and are targets for MDG (Millennium development goal) achievements.…”
Section: Introductionmentioning
confidence: 99%
“…An additional risk is exposure to pathogenic fecal coliform bacteria, which is common in rural areas of LMICs, due to poor sanitation and environmental conditions (D'Alonzo & Garsman, 2020; Lang, 2015). Children who experience growth stunting early in life are also at greater risk for obesity and obesity-related diseases in adulthood (De Lucia Rolfe et al, 2018;Lee et al, 2017). Researchers found that early-life nutrition interventions have long-lasting positive impacts on cognitive and psychological status (Ramírez-Luzuriaga et al, 2021a, 2021b, 2021c.…”
Section: Risks Associated With Malnutritionmentioning
confidence: 99%
“…Guatemala is an upper‐middle‐income country (UMIC) with one of the highest malnutrition rates worldwide 1 . It is also, simultaneously, undergoing a rapid nutrition transition, leading to an increasing prevalence of overweight (31.9%) and obesity (20.0%), while stunting is still high (47%) 2,3 . Malnutrition disproportionately affects rural areas, where most of the population is indigenous Maya 4 .…”
Section: Introductionmentioning
confidence: 99%